Enhancement of NMP Degradation Under UV Light by Nitrogen-Doped TiO2 Thin Films Using a Design of Experiment - F. Arefi-Khonsari; F. Meshkini; R. Jafari; H. Mortaheb; J. Pulpytel; W. Smith; H. Fakhouri; A. Zolfaghari (Журнал нано- та електронної фізики)
Doping nitrogen within TiO2 is an effective way to enhance visible light photocatalysis due to a direct electron excitation from the N2p states within the band gap. However, nitrogen doping is not always efficient for UV photocatalytic activity. Here, different structures of N-doped TiO2 (TiOxNy) have been prepared by reactive RF (13.56 MHz) magnetron sputtering. The morphological, optical, structural, and photocatalytic properties of the films have been studied in order to investigate the competitive effect of the morphology and the chemical composition on the efficiency of the photocatalytic activity. The variation of surface wettability of the film over time in the dark and under visible and UV irradiation was also studied. The reduction in wettability by dark storage can be explained by the adsorption of hydrocarbon contamination on the thin film’s surface. Additionally, from water contact angle experiments, it was found that these films developed hydrophilic properties upon UV and visible illumination. The photoinduced change in the contact angle of water was due to the removal of hydrocarbon contamination on the surface and also the photo-oxidation of the water droplet. Samples prepared at high pressure gave the best photocatalytic activity, even though the deposition rate was lower at higher pressures (lower film thicknesses), due to the high specific surface area and the optimal presence of TiOxNy crystals in the lattice. However, at low pressure, the TiN crystals became more predominant, and acted as recombination centers for the photo-generated charge carriers. A design of experiments was used in order to optimize the deposition parameters to have the best photocatalytic activity. The high photocatalytic activity under UV light was found to be due to the introduction of discrete energy levels within the band gap, the increased sample wettability, and the higher specific surface area. However, the post annealing process did not effect the activity under UV irradiation. Using the response surface methodology, RSM, based on a design of experiment, DOE, we are able to achieve a good understanding of the complex processes involved in the deposition of the thin films and their effect on the photocatalytic activity.